Auditoría administrativa en la organización de mujeres indígenas y campesinas del norte de Cotopaxi “Sembrando Esperanza” (ong’s) de la parroquia Toacaso, cantón Latacunga, periodo del 1 de enero al 31 de diciembre 2010 - Chuquitarco Chicaiza, Iván Fernando (2016)
The present work on the development of an Administrative Audit is carried out it for the first time to Indigenous Women and Peasants Organization of North of Cotopaxi "Sembrando Esperanza" (ONG'S) of Toacaso Parish, Latacunga Canton, during period January 1rst to December 31rst 2010"., with the objective to optimize the administrative process, the execution of goals and outlined objectives and mainly the good use of the resources. For the development of this, we worked with the administrative group of Organization such as: the President, Vice-president, Secretary, Vocal, Administrator and two Technicians. They provided required, real and necessary information about the administrative state Organization in order to collect the audit application.